2023
DOI: 10.1021/acs.estlett.3c00156
|View full text |Cite
|
Sign up to set email alerts
|

Size-Resolved Elemental Composition of Respiratory Particles in Three Healthy Subjects

Abstract: The chemical composition of respiratory particles is of interest because the viability of any viruses and bacteria in the particles has been shown to depend on this factor. Using computer controlled scanning electron microscopy/energy dispersive X-ray spectroscopy (CCSEM/EDX), we analyzed the size-resolved chemical composition of greater than 35,000 individual respiratory particles collected from three healthy human subjects, quantitatively at nanometer-scale spatial resolution. The desiccated particles ranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Mucin is a major component of saliva, though its exact concentration in saliva varies constantly due to many complex biological factors in the oral environment . NaCl and KCl are the major inorganic salt components in saliva. , Thus, the dominant components of the artificial saliva used in this study were mucin, NaCl, and KCl (a full description of its contents can be found in the Supporting Information, Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucin is a major component of saliva, though its exact concentration in saliva varies constantly due to many complex biological factors in the oral environment . NaCl and KCl are the major inorganic salt components in saliva. , Thus, the dominant components of the artificial saliva used in this study were mucin, NaCl, and KCl (a full description of its contents can be found in the Supporting Information, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…16,23−27 This finding illustrates the importance of investigating particles of interest at their actual sizes as both particle properties and composition can vary depending on their size. 28 Respiratory particles are expelled in a range of sizes, from large droplets (>5 μm) to fine (<2.5 μm) and ultrafine (<0.1 μm) aerosols. 29 While ultrafine particles are smaller than most respiratory viruses themselves, evidence exists that fine aerosols contribute to respiratory virus transmission, including measurements of influenza viral gene copies in aerosols produced by patient coughs that found that >42% of gene copies were in submicron particles (<1 μm).…”
Section: Introductionmentioning
confidence: 99%
“…If the study aims also to determine the distribution of viruses within respiratory particles, then the composition and PSD should be similar to those of respiratory particles. Additionally, compared to bulk respiratory fluid solutions, respiratory aerosols ,, appear to have enriched organic concentrations. This organic enrichment is affected by the particle size and method of aerosolization, ,, which can lead to small particles being disproportionately enriched in organics.…”
Section: Generation Of Virus-laden Particlesmentioning
confidence: 99%
“…For example, it is hypothesized that a virion that is embedded in an organic-enriched phase within a particle may experience inactivation rates different from those of a virion that is embedded in an inorganic-rich phase. At present, the morphology and composition of respiratory particles are not well understood, and it is not clear how viruses will partition within evaporating and equilibrated particles. ,,, Further, the role of surfactants on expiratory particle morphology and virus viability is poorly understood . The composition and partitioning of virions within a bulk solution and a particle are likely different, although the mechanisms that cause inactivation of the virions are not expected to differ, and so, it is important that further work is done to understand the composition and morphology of both respiratory particles and cell culture media particles.…”
Section: Trends In Virus Viability Experimentsmentioning
confidence: 99%
“…The choice of appropriate measurement techniques, including a combination of data from several instruments and empirical correction factors for evaporation and deposition, becomes particularly important when applied to the study of aerosols originating from the respiratory system [41]. However, a critical research gap lies in our understanding of aerosol size distribution within the airways themselves [42]. By adapting the methodology proposed here to focus on airway aerosols, a more accurate characterization of size distribution can be achieved, enabling researchers to extract meaningful results from a range of measurement instruments.…”
Section: Applicationsmentioning
confidence: 99%